Speech Rate and Sentence Length’s Influence on Perception of Mandarin Tone Sandhi - Xueke Yang (Studies in Social Science & Humanities, 2023)
It is well known that in Mandarin, the first low tone (T3) changes to a Rising tone when two low tones occur in an uninterrupted succession. It was discovered that Mandarin speakers could not distinguish the second tone from the third tone regardless of speech rate. People could not perceive the small pitch difference between the sandhi tone and the underlying tone 2 found in the production experiment. Speech rates at which the phrases were spoken did not affect the identification of the phrases. This study aims to investigate if the speech rate and sentence length really influence the perception of sandhi. A perception test is performed and 15 Mandarin speakers participated in the perception of the material. The identification differences under distinct speech rates and sentence lengths are significant. It is found that the sandhi tone is perceptually indistinguishable from tone 2, and speech rates and sentence length impact the identification of the sandhi.